2021
DOI: 10.1007/s15010-021-01650-5
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal transmission of SARS-CoV-2 and transfer of maternal IgG/neutralizing anti-SARS-CoV-2 antibodies from mothers with asymptomatic infection during pregnancy

Abstract: Purpose COVID-19 pandemic remains a serious public health threat worldwide. In view of the limited data on the risk of perinatal transmission of SARS-CoV-2 and transfer of maternal anti-SARS-CoV-2 antibodies, the present study was undertaken. Methods A prospective study including 57 pregnant women with a positive SARS-CoV-2 RNA test (SARS-CoV-2-RNA+) and 59 neonates born to them was conducted at Pune, India. 39 viral RNA negative (SARS-CoV-2-RNA-negative) pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…RBD-specific IgM and IgA were also measured in the cord blood; however, as these isotypes do not vertically transfer, titers were significantly lower in cord blood compared with maternal blood (Supplemental Figure 1G), and not significantly different from unexposed pregnancy cord blood (Supplemental Figure 1E). Our findings verify reports that SARS-CoV-2 IgG antibodies (30,32,39) and neutralizing antibodies (40,41) cross the placenta, providing a layer of immunity against SARS-CoV-2 infection to the neonate.…”
Section: Resultssupporting
confidence: 90%
“…RBD-specific IgM and IgA were also measured in the cord blood; however, as these isotypes do not vertically transfer, titers were significantly lower in cord blood compared with maternal blood (Supplemental Figure 1G), and not significantly different from unexposed pregnancy cord blood (Supplemental Figure 1E). Our findings verify reports that SARS-CoV-2 IgG antibodies (30,32,39) and neutralizing antibodies (40,41) cross the placenta, providing a layer of immunity against SARS-CoV-2 infection to the neonate.…”
Section: Resultssupporting
confidence: 90%
“…Joseph et al 2 in a well‐documented study on 32 paired samples (maternal and cord blood) did not show at the threshold of 14 days, a difference in the neutralizing potency but their findings concerned half of asymptomatic patients. Malshe et al 3 showed on nine infant mothers pairs a transfer of neutralizing activity beginning between 2 and 3 weeks after diagnosis.…”
Section: Case N° Ga At Diagnosis Ga At Delivery Pcr On Vaginal Secret...mentioning
confidence: 99%
“…If we postulate a similar immune response between natural infection and vaccination, 3 then the vaccination process should end 3 weeks before parturition. Considering the mRNA vaccine calendar the first injection should not be after 32 GA.…”
mentioning
confidence: 99%
“…6g). And the comparison of asymptomatic infection in pregnancy is quite high [62][63][64][65][66] (Fig. 6h), which proves the important role of ACE2 in asymptomatic infection.…”
Section: High Expression Of Ace2 Increases the Probability Of Asympto...mentioning
confidence: 92%